Guidance in Creating Differentiated Instructional Modules and Technology-Based Learning Media at State Elementary School 06 Ladang Padi Surian - Rahmatul Hayati; Prima, Wahyu; Wulandari, Suci; Yunita, Andini Putri; Gusteti, Meria Ultra; Widdya , Widdya (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Based on a preliminary study conducted at the Elementary Schools (SD) in Pantai Cermin Subdistrict, Solok Regency, it was found that the independent curriculum is being implemented independently because there is no primary school in Pantai Cermin Subdistrict serving as a leading school. Therefore, the implementation is still not optimal, especially in the development of differentiated teaching modules and differentiated teaching practices. The development of technology-based learning media, which supports the implementation of teaching, has also not been fully utilized, even though we cannot escape from technology in today's world. Hence, there is a need for assistance in the development of differentiated teaching modules, focusing on the subject of mathematics in elementary schools, and the utilization of technology as a learning resource in SD. This community service project will be conducted at SDN 06 Ladang Padi Surian in Pantai Cermin Subdistrict, Solok Regency. The approach used will be mentoring provided to the teachers at SDN 06 Ladang Padi. Through this mentoring, it is expected that teachers will be able to independently develop teaching modules and utilize technology as a learning resource, making the learning process meaningful and aligned with the characteristics of the students. The outcome of this mentoring program will be the creation of differentiated mathematics teaching modules and technology-based learning media, which can serve as guidelines for classroom instruction for teachers.